Influence of nutrients on biomass and oil yield from microalgae Chlorella vulgaris for biodiesel production (Revista Ciência Agronômica, 2019)
Microalgae are commonly used in aquiculture as feed for postlarval mollusks, fish and crustaceans becausethey are easy to grow, small in size, grow rapidly and have high levels of fatty acids. These microorganisms also accumulatehigh amounts of oil, which can be extracted and converted into biodiesel using chemical processes. In this work, freshwatermicroalgae Chlorella vulgaris was grown in the Live Food Production Laboratory (LABPAV/IFCE Aracati Campus), with urea(stock solution 1), triple superphosphate (stock solution 2) and vitamins (stock solution 3), in growth medium, in triplicate,using three different quantities of stock solutions 1 and 2, but with a constant amount of vitamins. The quantities of 0.5, 1 and2 mL (T0.5, T1 and T2, respectively) were used for both stock solutions. We then monitored the growth of the microalgae,flocculated through chemical flocculation by adding a NaOH 2N solution, air-oven dried at 60 ºC for 24 hours, weighed thedried biomass on a semi-analytical balance, and extracted the oil using solvents. We thus observed that algal growth intensifiedand dry biomass increased as the amount of nutrients increased in the growth media; inversely, the best oil level was observedin the treatment using the lowest amount of nutrients in the growth media where the microalgae developed (20.13±0.19%).Finally, in Treatment T2, even with the lowest percentage of oil (18.95%), the amount of biomass produced compensates in theoil productivity, and using a lower amount of nutrients in the media of culture.